INVESTMENT ENVIRONMENT AND DEVELOPMENT POLICY OF ENTERPRISES IN SERBIA - Aničić, Dušan; Nestorović, Olgica; Andjelković, Danijela (Journal of process management and new technologies, 2021)
Despite significant growth rates of over 4% in 2018 and 2019, the Serbian economy still lags far behind developed countries in terms of productivity, competitiveness and other business performance indicators. In the future, the main drivers of economic growth must be investments and exports, and consumption must grow more slowly relative to GDP. Opportunities for increasing GDP exist, and one of them is the increase of public investments that have a positive effect on the growth of the rest of the economy. Empirical research has shown that countries that have higher domestic savings have higher investments and faster economic growth. Also, the development of the country must not be based only on the growth of FDI, because, in addition to the positive ones, they also have great negative effects on the growth and long-term sustainable development of the domestic economy.